Conversation in the World of Polarized Social Conflicts. What Practical Lessons Emerge from the Philosophy of Dialogue in the Face of the Phenomenon of Social Polarization? - Filipiak, Magdalena (Sensus Historiae, 2024)
The tips inherent in the philosophy of dialogue turn out to be very current, especially in polarizing conflicts. Social polarization is defined as a deep conflict between specific groups of people, which, in its extreme version, makes it impossible to reach an agreement through rational argumentation. The radicalization of social polarization has several negative consequences. These include the escalation of violence, manipulation and social inequality. In this perspective, it seems necessary to complement the discourse with lessons from the philosophy of dialogue, such as responsibility for other people, positive evaluation of differences, or nonintermediation of interpersonal contacts. These ideas indicate a chance and possibility of achieving consent without resorting to violence, because they stem from the original understanding of relationships between people as an autotelic value.